Mountain Logistics: A Systematic Literature Review and Future Research Directions - Mehari Beyene Teshome; Faisal Rasool; Guido Orzes (Logistics)
Background: The sustainable development of mountain areas, which have fragile ecosystems, has increasingly attracted the attention of researchers and practitioners. Logistics systems are crucial in supporting these regions and addressing mountainous terrain’s unique challenges. While many studies have examined aspects of mountain logistics, a comprehensive and systematic review of the field is still lacking. Design/Methodology/Approach: This paper aims to fill the gap by systematically reviewing the existing literature on mountain logistics using the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) methodology. Results/Conclusions: We identify four main research foci: design of logistics infrastructure or vector, optimization of logistics systems, safety in logistics systems, and impact of logistics systems on mountain communities. In addition to categorizing these themes, we conduct a detailed descriptive analysis of published studies in this domain. Our findings highlight significant research gaps, particularly in integrating digital technologies, sustainable mass transportation solutions, and logistics systems’ socioeconomic and environmental impacts. We propose targeted directions for future research to advance sustainable logistics practices in mountain regions.